Optimal design of water distribution networks - Bhave, P ramod R. (Alpha Science International, 2003)
In case of water distribution networks, engineers are concerned with two aspects: Analysis of networks for operational purposes, and as an intermediate step in design by the traditional trial-and-error apporoach; and economical design of new networks, and strengthening and expansion of existing ones.